The Influence of Tangible, Reliability, Responsiveness, Assurance, and Emphaty on Customer Satisfaction at PT PLN Persero - Tuzahra, Siti Mutia; Megawati, Megawati (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to analyze the effect of Tangible, Reliability, Responsiveness, Assurance, and Empathy on Customer Satisfaction at PT PLN Persero. This study uses quantitative methods and a sample of 100 respondents. Methods of data analysis using non-probability sampling, purposive sampling and multiple regression with the SPSS ver 26 test tool. Based on the results of the study, it shows that only the Reliability variable has a partial effect on Customer Satisfaction at PT PLN Persero and the Tangible, Responsiveness, Assurance, and Empathy variables have no partial effect on Customer Satisfaction at PT PLN Persero. Simultaneously each variable, namely Tangible, Reliability, Responsiveness, Assurance, and Empathy has an positive effect on Customer Satisfaction at PT PLN Persero.